Karakteristik Sensori, Kimia dan Fisik Pempek dari Ikan Tenggiri dan Ikan Kiter pada Berbagai Formulasi - Esa Ghanim Fadhallah; Fibra Nurainy; Erdi Suroso (Jurnal Penelitian Pertanian Terapan, 2021)
Pempek is one of the traditional snack food from Palembang which is made from fish and very popular in Indonesia. The objective of this study was to determine the effect of the combination of barred mackerel fish and pick handle barracuda fish meat on sensory, chemical, and physical properties and to determine the best economic formulation of pempek. This study used the Completely Randomized Design with six-level treatments of a combination of barred mackerel fish and pick handle barracuda fish, respectively, 200 g-0 g (P1), 160 g-40 g (P2), 120 g-80 g (P3), 80 g-120 g (P4), 40 g-160 g (P5), and 0 g-200 g (P6). The characteristics of pempek were observed on the sensory (color, aroma, taste, texture, and overall acceptance), chemical (moisture and protein content), and physical properties (hardness, cohesiveness, springiness). The result showed that the treatment only has a significant effect on the color parameter of sensory properties. The higher amount of use of pick handle barracuda fish significantly reduced the panelist preference on color. The best formulation chosen was the combination of 40 g barred mackerel fish and 160 g pick handle barracuda with an economic total raw material cost of Rp 12.750. This formulation is recommended to produce pempek with the best quality and economic cost.